2020
DOI: 10.1177/0011000019898583
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Acculturation and Enculturation: Bilinear, Multidimensional, and Context-Dependent Processes

Abstract: Acculturation and enculturation are currently conceptualized as bilinear, multidimensional, and context-dependent cultural socialization processes (Yoon et al., 2013). Yet, this conceptualization requires further specification and empirical evidence. Our work is timely given the downward shift in productivity of traditional acculturation research and the need for a new direction. We examined the constructs and processes of acculturation and enculturation by meta-analytically synthesizing the findings of 255 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 68 publications
(123 reference statements)
1
38
1
Order By: Relevance
“…Instead, one's social, political, and economic context should be considered. Understanding acculturation from interaction with one's context was supported by Yoon et al (2020), who confirmed the process of acculturation and enculturation was interactive with social context.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Instead, one's social, political, and economic context should be considered. Understanding acculturation from interaction with one's context was supported by Yoon et al (2020), who confirmed the process of acculturation and enculturation was interactive with social context.…”
Section: Discussionmentioning
confidence: 92%
“…The results from this study show that the scores in the three areas of the acculturation process in U.S. and Chinese domains are positively correlated, providing evidence that acculturation could be bi-directional, rather than unidirectional. A recent meta-analysis result by Yoon et al (2020) supported the bilinear relationship and multidimensionality of acculturation and enculturation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…socializing with others does not necessarily mean adopting their values or identifying with them, or high levels of language proficiency does not guarantee adherence to cultural values; Miller & Kerlow‐Myers, 2009; Nguyen & Benet‐Martinez, 2007; Phinney & Ong, 2007; Selmer & de Leon, 1993; Tsai et al., 2002) and may differ in their rate of development (e.g. behaviours in the form of language use may occur faster than changes in values; Kim et al., 1999; Yoon et al., 2020). For this reason, it is important to indicate the domain of interest when conceptualizing and operationalizing the domain‐specificity aspect of acculturation.…”
Section: How To Study Acculturation: Review Of Conceptualization and Operationalizationmentioning
confidence: 99%
“…Excluded is also a multiculturalism perspective, which focuses on identity as a sense of belonging and emotional attachment to one or more cultural groups (e.g. Benet‐Martínez and Haritatos, 2005; Phinney and Ong, 2007) and the internalization of cultural knowledge, values and schemas (for a review, see Vora et al., 2019). According to the multicultural perspective, the acculturation process operates similarly for anyone who has internalized more than one culture, whereas the NWS perspective emphasizes the differences in acculturation processes for cultural minority versus majority members.…”
mentioning
confidence: 99%